2018
DOI: 10.1021/acs.jcim.7b00640
|View full text |Cite
|
Sign up to set email alerts
|

Role of Molecular Interactions and Protein Rearrangement in the Dissociation Kinetics of p38α MAP Kinase Type-I/II/III Inhibitors

Abstract: Understanding the governing factors of fast or slow inhibitor binding/unbinding assists in developing drugs with preferred kinetic properties. For inhibitors with the same binding affinity targeting different binding sites of the same protein, the kinetic behavior can profoundly differ. In this study, we investigated unbinding kinetics and mechanisms of fast (type-I) and slow (type-II/III) binders of p38α mitogen-activated protein kinase, where the crystal structures showed that type-I and type-II/III inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 81 publications
2
21
0
Order By: Relevance
“…From the loading plot, it can be deduced that larger molecular volume contributes to longer residence time, while stronger hydrophilic interactions contribute to faster dissociation (Figure 7d). The result proposed in this study is consistent with previous researches, which suggested that type I kinases inhibitors bind to the ATP binding site and usually smaller and faster, while compounds of type II are generally large since occupy additional transient sub-pocket [36,37].…”
Section: Volsurfsupporting
confidence: 92%
“…From the loading plot, it can be deduced that larger molecular volume contributes to longer residence time, while stronger hydrophilic interactions contribute to faster dissociation (Figure 7d). The result proposed in this study is consistent with previous researches, which suggested that type I kinases inhibitors bind to the ATP binding site and usually smaller and faster, while compounds of type II are generally large since occupy additional transient sub-pocket [36,37].…”
Section: Volsurfsupporting
confidence: 92%
“…Additionally, p38α MAPK inhibitor dissociation has been investigated by simulations. For instance, dissociation pathways of type I and type II inhibitors were evaluated utilizing accelerated MD 25 and unbinding of a type II inhibitor was studied by the metadynamics approach 11 . Moreover, dissociation of selected type I and type II inhibitors were studied by steered MD 10 .…”
Section: Introductionmentioning
confidence: 99%
“…7 It requires a well-defined reaction coordinate (RC) represented by one or a few variables. 1113 Intensive conformational sampling is performed by enforcing external restraints at the conformations along the RC within a series of successive overlapping windows. Finally, the PMF can be constructed by removing the external restraints.…”
Section: Introductionmentioning
confidence: 99%